The application of perfluoroheteroaromatic reagents in the preparation of modified peptide systems12. Issue 19 (4th May 2017) - Gimenez, Diana; Mooney, Caitlin A.; Dose, Anica; Sandford, Graham; Coxon, Christopher R.; Cobb, Steven L.
Abstract : A one-step peptide-modification using perfluoroheteroaromatics can deliver enhanced proteolytic stability in pharmaceutically relevant peptides such as oxytocin. Abstract : The perfluoroheteroaromatic reagent pentafluoropyridine has proved to be a highly reactive electrophile, undergoing SN Ar arylation reactions in the presence of a range of nucleophilic peptide side chains ( i.e. cysteine, tyrosine, serine and lysine) under mild conditions. Moreover, we have shown how one-step peptide-modification using perfluoroheteroaromatics can deliver enhanced proteolytic stability in pharmaceutically-relevant peptides such as oxytocin.